Risk of Peptic Ulcer Bleeding Associated with Infection, Nonsteroidal Anti-inflammatory Drugs, and Low-dose Aspirin Therapy in Peptic Ulcer Disease: A Case-control Study - Seung In Seo; Jin Gu Kang; Hyoung Su Kim; Woon Geon Shin; Myoung Kuk Jang; Jin Heon Lee; Hak Yang Kim (Yong Chan Lee, 2019)
Background/Aims The association between Helicobacter pylori infection and nonsteroidal anti-inflammatory drugs (NSAIDs) or low-dose aspirin therapy as a risk factor for peptic ulcer bleeding (PUB) remains unclear. This study investigated the risk of PUB associated with H. pylori infection and NSAID or low-dose aspirin therapy in patients with PUD. Materials and Methods This case-control study investigated 340 patients with PUB between 2012 and 2016. The control group comprised age and sex-matched patients with endoscopically documented non-bleeding ulcers. Using logistic regression analysis, the adjusted odds ratio (AOR) was calculated for the risk of PUB. Results Of the patients investigated, 57.9% in the study group and Results Of the patients investigated, 57.9% in the study group and 51.8% in the control group were diagnosed with H. pylori infection (P=0.106). Logistic regression analysis showed synergistic interaction between H. pylori infection and low-dose aspirin therapy. Multivariate analysis showed that low-dose aspirin (AOR 3.92, P=0.001), NSAIDs (AOR 2.98, P=0.001), warfarin (AOR 14.57, P=0.011), gastric ulcer (compared with duodenal ulcer) (AOR 1.65, P=0.01), and smoking (AOR 1.97, P=0.004) increased the risk of PUB compared with the risk of PUD.Conclusions: Both NSAIDs and aspirin are independent risk factors for bleeding in patients with PUD. Additionally, low-dose aspirin therapy concomitant with H. pylori infection produced a synergistic effect. Therefore, H. pylori eradication may be crucial in aspirin users. Moreover, a proton pump inhibitor should be prescribed in patients with a history of bleeding ulcers who need long-term NSAID treatment.